Speech by the Vice-Chancellor, Y. Bhg. Datuk Musa Mohamad, at the Opening Ceremony of the Workshop on Microcomputer Courseware Education in Science and Mathematics Education on Monday, 20 August 1984, at 8.45 a.m. at the Viewing Room, Educational Technology Unit, Universiti Sains Malaysia - Mohamad, Musa (Penerbit Universiti Sains Malaysia, 1984)
Let me begin by thanking most warmly APEID and UNESCO for having so generously sponsored Professor Shinohara to run this workshop on microcomputers in education and also to thank Professor Shinohara himself for agreeing to come and make his expertise available to us inspite of the numerous international commitments which he has to fulfill. I would also like to take this opportunity to welcome particularly those of you from outside this University and from overseas, to the USM campus with the hope that you will have a most fruitful and worthwhile experience at this workshop.